Remote sensing applications for rice production monitoring in Senegal 2024 - Murugesan, Deiveegan; Quicho, Emma; Mathieu, Renaud; Faye, Omar Ndaw; Kane, Babacar; Sall, Moussa; Gatti, Luca; Holecz, Francesco (International Food Policy Research Institute, 2024)
Rice is a fundamental staple food in Senegal and many parts of West Africa, where it holds significant cultural, economic, and food security importance. Despite its vital role in the nation’s di and agricultural landscape, rice cultivation in Senegal has struggled to keep pace with rising consumption, and the country has imported most of the rice it consumes for many years. Most rice production occurs in the Senegal River Valley (SRV) in the northern region, where it is cultivated under intensive, irrigated systems. The Casamance region in the south mainly relies on rainfed rice farming. To achieve the goal of self-sufficiency, reduce imports, and encourage economic grow Senegal is taking many interventions to improve their rice production, while monitoring rice area and production estimates is crucial for designing/targeting interventions and for making sound policy decisions. As part of the ‘CGIAR Initiative: Digital Innovation’, IRRI is developing a digital platform for rice production monitoring for Senegal, with sarmap, Switzerland, and the Institut Sénégalais de Recherches Agricoles (ISRA). The goal is that the tool can be transferred to and implemented in Senegal Institutions to ensure long-term monitoring of rice crop production. The team first selected the SRV and irrigated lands for the pilot initiated in 2023 and extended the pil in the rainfed region of Casamance in the 2024 wet season. This report presents the activities and results of the development of the platform, including rice areas and yield, across Senegal during 2023-24 using the remote sensing-based Information and Insurance for Crops in Emerging Economies (RIICE) technologies.